ASSISTING PREGNANT WOMEN'S CLASSES IN AN EFFORT TO IMPROVE MATERNAL AND INFANT HEALTH IN THE GARUT CITY AREA - Rosita Alvia, Rosita Alvia; Titi Purwitasari Handayani, Titi Purwitasari Handayani; Mellysa Wulandari Tasripin, Mellysa Wulandari Tasripin; Annisa Devi Permata, Annisa Devi Permata; Ni’ma Nur Insani Yayu Putri, Ni’ma Nur Insani Yayu Putri; Rahmi, Rahmi; Lina Humaeroh, Lina Humaeroh; Fitri Hanriyani, Fitri Hanriyani (Jurnal Pengabdian Masyarakat DEDIKASI, 2023)
Garut Kota is a sub-district in Garut Regency, West Java, Indonesia. Although this sub-district is called Garut Kota, the center of government of Garut Regency is in Tarogong Kidul Sub-district. Pregnancy is a continuous chain that starts from ovulation until the growth and development of the conception in the uterus. Pregnancy is a natural process, but proper care must be taken so that the mother and fetus are healthy. One of the efforts to improve maternal health during pregnancy through an approach is the class of pregnant women. The involvement of STIKes Karsa Husada Garut as one of the stakeholders in the class of pregnant women is intended to be able to actively participate in the program to increase the knowledge and skills of pregnant women regarding pregnancy, pregnancy care, childbirth, postpartum care, infant care, myths, infectious diseases and birth certificates through pregnant women's class activities. This activity for STIKes karsa Husada is a community service activity which is one of the obligations of Higher Education Institutions in carrying out Tri Dharma. The implementation of activities at the Garut Square Hall, on Saturday, February 03, 2024. Participants were attended by 30 pregnant women in the Garut City area.